Pelayanan Perpustakaan Keliling Dinas Perpustakaan dan Kearsipan Kota Pekanbaru - Hendry Andry; Rava Joti; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
This study aims to determine the inhibiting factors for library service of Pekanbaru City Library and Archives Service employees in carrying out mobile library services. The problems in this study are The lack of a mobile library car fleet so that access to library services is not evenly distributed to all levels of Pekanbaru City society, and also the lack of a number of officers who provide services and officers who have skills and abilities, officers have not been able to think and act innovatively. so that people are less interested in using mobile library services, Limited supporting facilities such as collections of books, tables, and chairs so that it does not provide comfort for people who visit to read books. This research uses descriptive quantitative method. Data obtained through observation, questionnaires, interviews, and documentation. Based on the results of the study, it can be concluded that the library service of Library and Archive Service Employees in Mobile Library Services has not been maximized or good enough. The cause are facilities and infrastructure, human resources who have very minimal skills and abilities, employees or officers are less consistent in carrying out their duties. The suggestions are 1. Increase the fleet, books, tables and chairs so that the purpose of the mobile library service program is to improve the reading culture of the community can be achieved effectively and efficiently, 2. Recruit employees who have a background in library science so that these human resources can provide better services optimally